Predictors of Resuming Therapy Within Four Weeks after Discharge from Inpatient Rehabilitation - Ostwald, Sharon K. (2009)
PURPOSE: 1) Identify the percentage of persons with stroke resuming therapy within four weeks of inpatient rehabilitation discharge, 2) compare the characteristics of those who did and did not resume therapy, and 3) determine the predictors of resuming physical (PT), occupational (OT), and speech (ST) therapy. METHOD: Socio-demographic, stroke-related, and therapy data for persons with stroke (n=131) were abstracted from inpatient rehabilitation charts. Functional Independence Measure, Stroke Impact Scale, Geriatric Depression Scale and data on therapy received after discharge were also collected. RESULTS: Logistic regression models demonstrated that minorities were less likely to resume PT (OR=.30) and OT (OR=.25). Survivors with neglect/visual-field cut/spatial-perceptual loss were 2–3 times more likely to resume PT, OT, and ST. Survivors with higher scores on the SIS Physical domain sub-scale were less likely to resume PT (OR=0.98) and OT (OR=0.97). Men were 3.3 times more likely to have OT than women. Those with comprehensive health insurance were 11.2 times more likely to receive ST. CONCLUSIONS: The benefits of outpatient therapy are not universally available to all persons with stroke. Further research needs to explore the factors that hinder the prompt resumption of therapy for minority and female persons with stroke and to test appropriate interventions.